Posterior Wall Acetabulum Fracture with a Persistent Sciatic Artery: A Case Report. Issue 3 (July 2021) - Chang, Gerard; Chip Routt, Milton L.; Warner, Stephen
Abstract : Case: We report the case of a patient who sustained a left posterior wall acetabular fracture with an ipsilateral persistent sciatic artery (PSA). The PSA was diagnosed preoperatively on lower extremity computed tomography angiogram. He was treated with open reduction internal fixation through a Kocher-Langenbeck approach. The PSA and sciatic nerve were identified and protected throughout the case. There were no neurovascular complications. Conclusion: PSA in the setting of posterior wall acetabulum fractures has not been reported previously. Orthopaedic surgeons who treat these injuries should be aware of PSA anatomic variants so that they can be identified and protected during surgery.